Radiação obscura: fluxos energéticos sonificados no limiar da experiência sonora - Paquete, Hugo (2021)
This essay analyse the impact of the sonification processes in the sound arts. This is achieved exploring the definition of their production methodologies, philosophical implications and conceptual significance taking as examples my artistic experiments with sonification of light and electromagnetic fields explored in my projects that are presented in this analyses. The sonification as an artistic practice consist of generating art works based in the data-flows. Originated a sound event outside the physic of sound as non-vibration force. That is associated in my argument as data-event-sound connected with a new ontology outside the forces that animate the understanding of sound as vibration. Opening the understanding of the work of art as a system of interdependent relations in digital-art. Generating new ways of understanding sound as mutation in which digital, culture and spiritual establish interconnections between the computer as a digital domain in a landscape of code, promoting complex regimes of laminar-perception.